A Landscape of Memories through the Music of Hope Lee - Feliz, Juro Kim (Nomadic Sound Worlds, 2018)
Produced by Juro Kim Feliz under the Canadian Music Centre Library Residency, Nomadic Sound Worlds is a four-part blog/podcast series exploring Canadian contemporary music through the lens of present-day global migration. A collection of essays named Letters of Transit: Reflections on Exile, Identity, Language, and Loss (ed. André Aciman, 1999) informs and inspires this project, with trajectories branching out from related themes including mobility, displacement, loss, reconciliation of polarized truths, and invention of selves. In this regard, the series will feature selected immigrant Canadian composers whose musical worlds collide with various personal stories of immigration.

Ana Sokolović. Robots musicaux et kolo serbe - Harman, Brian (La création musicale au Québec, 2018)

Jazz, gender, historiography: a case study of the "Golden Age" of jazz in Montreal (1925-1955) - Blais-Tremblay, Vanessa (Université McGill, 2018)
This dissertation maps the interaction between jazz, identity, modernity and nation during the so-called "golden age" of jazz in Montreal (1925-1955). Drawing on the fields of musicology, women's studies (black feminist theory and feminist research methods in particular), critical dance studies, and cultural studies, this project provides a critical re-writing of the history of Montreal jazz, one which acknowledges various roles that racialized and ethnicized women played in the shaping of modern identities, pleasures and sounds in Quebec. Montreal's particular status as a "showtown" makes it a rich laboratory to study the collaborative creative relationships between jazz music and dance on the black variety stage in the first half of the twentieth century. I also map the specific parameters that articulate the discursive relationship between jazz and vice, in particular as these relate to the gendered and racialized embodiment of morality in interwar Quebec. Finally, this dissertation produces the first extensive biographical accounts and critical listening of several prominent Montreal-based female jazz artists, including pianists Vera Guilaroff and Ilene Bourne, all-girl groups such as The Spencer Sisters and the Montreal Melody Girls Orchestra, black women performers such as Tina Baines Brereton, Bernice Jordan Whims, Marie-Claire Germain, Mary Brown, Natalie Ramirez, as well as piano teacher Daisy Peterson Sweeney and dance teachers Ethel Bruneau and Olga Spencer Foderingham.

Entrevista com a cantora e compositora Bïa Krieger [Entretien avec l'autrice-compositrice-interprète Bïa Krieger] - Cassiano, Raissa (Tradterm, 2018)
Radicada há mais de vinte anos na França e no Canadá, Bïa Krieger conquistou um público cativo nesses países, onde recebeu prêmios importantes, como o Grand Prix de l’Académie Charles Cros (França), Prix de l’Adisq (Canadá) e Félix du Meilleur Album Musiques du Monde (Canadá). Esta entrevista contempla o seu trabalho como versionista, com enfoque nas versões em francês para canções de Chico Buarque.

Lhasa de Sela et la traversée des espaces - Proulx, Robert (Archiv für Textmusikforschung, 2018)
The singer-songwriter Lhasa de Sela (1972-2010) launched her career and produced her three records in Montreal where she arrived in 1991. Not only did she change the face of migrant song in Quebec, but she also enjoyed international success, embarking on long world tours and selling more than a million records. This analysis will focus on the songs from her second album, The Living Road, and will show that Lhasa de Sela transcended linguistic and artistic frontiers by crossing the geographical border when she made Montreal her home and creative hub.

Music from the Wrong Place: On the Italianicity of Quebec Disco - Straw, Will (Criticism, 2018)
One of my favorite compilation CDs of the last few years is Unclassics: Obscure Electronic Funk and Disco, 1975–1985, released in 2004 on the Environ label. The thirteen tracks on Unclassics were collected and remixed by house/techno artist Morgan Geist, who offers them as all-but-forgotten dance music gems from just outside an Anglo-American musical axis, from places like Spain and Italy. The style that ostensibly unites these tracks is “Eurodisco,” though, as we shall see, that label does not accurately subsume all of them. “Italo-disco” seems an even cruder reduction, but circulates among critics, fans, and collectors as a meaningful label for much of the music gathered here. While some of the cuts on Unclassics have long been the idiosyncratic favorites of DJs or dance music collectors, more is going on here than the resurrection of cultish or neglected treasures. Unclassics is one milestone within the significant rehabilitation of European and Italian disco that has unfolded over the last decade. Mixed Up in the Hague, Vol. 1, a compilation first released privately in 1999, was a key event in this rehabilitation; other collections, like I-Robots: Italo Electro Disco Underground Classics and Confuzed Disco: A Retrospective of Italian Records, have followed. Zyx, the Germany-based label that dominated the field in the 1980s and early 1990s, is actively marketing dozens of compilations of its own Italo-disco from that period. The garish red and green covers of Zyx’s Italo anthologies, which filled the discount cassette bins of European airport stores fifteen years ago, have been redesigned so that they now look authoritative and curatorial. Radio and DJ sets devoted to this music now abound on the Internet. Think Italy. Without claiming mind-reading powers, it’s a comfortable prediction you’ve already got tacky piano sample records and frenzied all-night clubbing in mind, a nation that when it isn’t knocking out club records by the cartload likes nothing more than to party all night on a hillside by the sea. Italian music has been in and out of style more often than the flares revival. There are enough piew-piew-piew zaps during these 55 minutes to wipe out a small nation of roller skaters. For almost two decades, tracks like those collected on Unclassics held the status of morbid symptoms, reminders of the decay and dispersion of dance music in the years between disco and house music. Even as they reclaim these tracks as lost gems, the liner notes to Unclassics embrace that morbidity, relishing the ways in which so many of these pieces are seen to have gotten things wrong. My favorite track on Unclassics is a Spanish cut from 1979, “Margherita,” whose guiltless dishing out of pleasures betrays the compilation’s broader sensibility. Piercing little synth notes alternate with thick, rolling movements that could drive an army forward. Mariachi horns interweave with tinny keyboard glissandos in rounding out sections. Changes come precisely when we want them; each gimmicky sound or flourish dutifully returns just as we start to miss it. As “Margherita” moves in unstoppable fashion around its wheel of styles and sections, it is easy to think that this is music trying too desperately to be liked. Dominant understandings of the European contribution to disco read its influence selectively, focusing on the robotic, synthesized sounds of Kraftwerk or Giorgio Moroder. These versions of Eurodisco’s history link such figures as Can, Patrick Cowley, Afrika Bambaataa, and Juan Atkins in a heroic story that sends disco to Europe so that it may return, reinvented, to an American underground able to realize its radical potential. When Eurodisco is remembered for its sleek mechanical control, however, what gets forgotten is the lush extravagance that seemed to mark so much of it. As early as 1977, North American critics had recourse to a well-entrenched moral geography in characterizing disco music from continental Europe as “florid,” given to flamboyant passion and bombastic overlays of effects.1 Arguably, the peculiarity of so much Eurodisco came from the ways in which its extravagant lushness often went hand in hand...